Policy work in Canada : professional practices and analytical capacities - Howlett, Michael, 1955-; Wellstead, A. M., 1967-; Craft, Jonathan, 1980- (University of Toronto Press, 2017)
"Policy Work in Canada is an in-depth study into the levels of analytical capacity found within the federal and provincial governments as well as the non-governmental sector. By focusing on the individuals who craft public policy in Canada, this collection of eighteen chapters broadens and deepens our understanding of policy development in Canada."--